PUBLIC RELATIONS AT UNIVERSITIES: MIDDLE EAST TECHNICAL UNIVERSITY AND BILKENT UNIVERSITY SAMPLES - DOĞAN, Okan (Atlas Journal, 2021)
The commercialization of education has initiated marketization in higher education. This change led to the emergence of market-centered financing and brought a competitive environment. Since then, universities have been known as commercial enterprises and academic identities. In this condition, public relations (PR) contributes to the development of mutual understanding in organisation-public relations as a management function helping universities achieve corporate reputation, image and financial gain. This thesis aims to examine the PR practices of Middle East Technical University (METU) and Ihsan Dogramaci (I.D.) Bilkent University. The data obtained through this study, which assumes the two-way symmetric model as an ideal PR model, were analyzed under four main themes; the hierarchical position of the PR units, publics and corporate PR perceptions of the universities and the PR methods of them. The in-depth interview method was chosen to collect the data and 36 structured interview questions were asked via face-to-face method and the Internet. The findings were analyzed using descriptive analysis method. As a result, differences in terms of the hierarchical positions of the units and in the definitions of the duties and responsibilities of the units are found. However, the institutions showed similarities in the public category classifications and communication preferences. Both universities use PR for branding and fund raising purposes; however, as a public university, METU differs from Bilkent University. There seemed no difference between their PR processes. It was understood that a definite PR model was not followed and PR was not accepted by the universities as a management function.